2019
DOI: 10.1002/jmv.25561
|View full text |Cite
|
Sign up to set email alerts
|

Significance of RANTES‐CCR5 axis and linked downstream immunomodulation in Dengue pathogenesis: A study from Guwahati, India

Abstract: We aimed to evaluate the significance of the RANTES‐CCR5 axis and resulting immunomodulatory status in Dengue pathogenesis involving a Guwahati, India based population where Dengue cases have increased alarmingly. An increased CC‐chemokine receptor type 5 (CCR5) messenger RNA expression and CCR5 positive cell count profile was observed in Dengue cases, the highest being in severe cases. CCR5 ligand RANTES expression was significantly decreased in Dengue cases and inversely correlated with Dengue viremia fold c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In the same direction, no effect of CCR5Δ32 on susceptibility to DENV infection was found in a small sample-size study performed with individuals from Western Australia (Brestovac et al, 2014) and recent data suggested no important involvement of CCR5 gene or CCR5 polymorphisms in DENV infection (Cahill et al, 2018;Ornelas et al, 2019). Finally, the CCR5Δ32 allele was not identified in a small group of Indian DENV-infected individuals (Islam et al, 2019). Table 6 shows some details of the studies involving CCR5Δ32 and DENV infection.…”
Section: Dengue Virusmentioning
confidence: 89%
See 1 more Smart Citation
“…In the same direction, no effect of CCR5Δ32 on susceptibility to DENV infection was found in a small sample-size study performed with individuals from Western Australia (Brestovac et al, 2014) and recent data suggested no important involvement of CCR5 gene or CCR5 polymorphisms in DENV infection (Cahill et al, 2018;Ornelas et al, 2019). Finally, the CCR5Δ32 allele was not identified in a small group of Indian DENV-infected individuals (Islam et al, 2019). Table 6 shows some details of the studies involving CCR5Δ32 and DENV infection.…”
Section: Dengue Virusmentioning
confidence: 89%
“…The immune response mediates DENV clearance and the resolution of dengue diseases, but it is also involved in the disease pathogenesis (Murphy and Whitehead, 2011). Some evidence suggests the participation of CCL5/CCR5 axis in the protection against DENV (Sierra et al, 2014), as well as in the pathogenesis of Dengue disease (Islam et al, 2019). Indeed, DENV infection is associated with increased frequency of human CCR5 + T cells (de-Oliveira-Pinto et al, 2012;Badolato-Corrêa et al, 2018).…”
Section: Dengue Virusmentioning
confidence: 99%
“…It is possible that the baseline RANTES level makes the protective capacity of cross-reactive immunity more effective. In a study with a dengue-predisposed population from Guwahati, India, it was suggested that expression of both RANTES and CCR5 has prognostic value in DENV infections through altered immunomodulation from the RANTES-CCR5 axis (20). Although the finding with RANTES was not statistically significant, we think that this is due to limited sample size; only 3 responders were available in the trivalent group, and our exploratory results could provide potential insights for future studies.…”
Section: Discussionmentioning
confidence: 73%
“…We found higher IP-10 induction in Black tetravalent vaccine recipients, perhaps explaining why Durbin et al (25) found reduced vaccine viremia in Black participants after vaccination. Islam et al suggest that DENV has a competitive edge of infecting the monocytes and initiating infection pathogenesis under a RANTES-deficient condition (20). Lower RANTES levels were found in White participants receiving trivalent admixture compared with Black recipients, contributing to a possible advantageous environment for DENV infection, which also potentially explains the a higher frequency of viremia in White volunteers following vaccination observed in Durbin et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…46 To compare the cyto- and chemokine profile of DENV vaccine strains, we utilized Multiplex ELISAs analyzed a panel of cyto- and chemokines (IFNα2, IL-10, IL-1β, Il-6, IL-8, IP-10, MCP-1, MIP-1β, RANTES, TNFα) that have been characterized to play an important role in DENV infection. 4751 We did not observe differences in the secretion between the vaccine viruses for IL-8, MIP-1β, TNFα, and RANTES (Supplementary Figure 1, A-E). However, the rDEN1Δ30 and rDEN4Δ30 vaccine strains showed significant induction of IFNα2 at 48 hpi (Figure 2(A)).…”
Section: Resultsmentioning
confidence: 83%